Synthesis and Physicochemical Characterization of Ce1−xGdxO2−δ: A Case Study on the Impact of the Oxygen Storage Capacity on the HCl Oxidation Reaction. Issue 22 (16th October 2015) - Möller, Maren; Urban, Sven; Cop, Pascal; Weller, Tobias; Ellinghaus, Rüdiger; Kleine‐Boymann, Matthias; Fiedler, Carsten; Sann, Joachim; Janek, Jürgen; Chen, Limei; Klar, Peter J.; Hofmann, Detlef M.; et al.
Abstract: This study reports the synthesis of high‐surface‐area Ce1− x Gd x O2− δ (CGO) fibers that are used as catalysts for the oxidation of HCl. Special emphasis is put on the role of the oxygen storage capacity (OSC) of the CGO fibers on the catalytic performance. An in‐depth physicochemical characterization of high‐surface‐area CGO was achieved by employing a multitude of dedicated spectroscopic techniques. The increasing OSC with Gd content is traced to the development of a space charge region with increased electron concentration as a result of the nano size of the CGO particles. The activity of CGO in the HCl oxidation reaction is shown to decrease with Gd concentration. Abstract : More storage, less activity : Doping of CeO2 nanoparticles by Gd in electrospun fibers affects the oxygen storage capacity but does not improve the activity in the catalytic oxidation of HCl.